Manajemen Strategi HIMMAH NWDI Komisariat STIT Palapa Nusantara dalam Meningkatkan Kemampuan Komunikasi dan Leadership Kader - Kamaruddin Kamaruddin (LP2M STIT Palapa Nusantara, 2025)
Although the development of communication and leadership skills in student organizations has been widely studied, research that specifically analyzes the strategic management approaches of HIMMAH NWDI as a youth organization grounded in religious values remains limited. This study aimed to explore the strategic management model of HIMMAH NWDI Komisariat STIT Palapa Nusantara in enhancing members’ communication competence and leadership capacity. The study employed a qualitative approach with a case study design and involved four key informants, namely the Komisariat Chair, Secretary, Head of Cadre Development, and a senior member. Data were collected through semi-structured interviews, direct observation, and analysis of organizational documents during 2024–2025. Thematic analysis identified five main strategic patterns: (1) strengthening communication through public speaking training, scholarly discussions, and dakwah rhetoric; (2) leadership formation through WAPA I, managerial training, and decision-making simulations; (3) strategic planning through Rapat Kerja and periodic evaluation; (4) implementing social activities as a medium for applied leadership; and (5) religious-ideological development through halaqah, Maulid, and internalization of NWDI character. The findings show that HIMMAH NWDI applied a hybrid strategic management model that integrates religious, intellectual, and managerial values in cadre development, indicating that strategic management plays an important role in sustaining continuous improvements in cadre quality. The study recommends strengthening digital communication training and collaborative leadership programs, provides a conceptual contribution to youth leadership studies in religious organizations, and offers a practical framework for developing a more structured, competency-oriented cadre system.